Depression and mental health literacy among elderly in Selangor - Zainal Abidin, Muhammad 'Adil; Rusli, Mohammad Farhan; Badrol Hisham, Afaf Qamelia; Abdul Khaiyom, Jamilah Hanum; Kadir, Hayati; Mahmud, Siti Mariah (2023)
Introduction: In Malaysia, one in three citizens suffers from mental health problems. According to Department of Statistic Malaysia (DOSM), the ageing population increased from 5% in 2010 to 6.8% in 2020. As the ageing population increasing, the burden of disease and their mental health literacy is a challenge. The Mental SEHAT module, embedded in the SELangkah application, is Malaysia’s first state-funded mobile application. It was introduced in 2021, offering a holistic approach to mental health issues. This study aims to measure the prevalence of depression among elderly in Selangor and its relationship with their mental health literacy. Methodology: In the SELangkah application, the Mental SEHAT provides validated questionnaires to screen users level of depression using GDS-15. A validated Malay version of the Mental Health Literacy Scale (MHLS) was used to measure the literacy level. Data was analysed using IBM SPSS Version 26. Data was collected from June 2022 until June 2023. Results: As of June 2023, 5189 users completed the screening. The mean age was 58 with the (Min 50, max 80). More than 79.8% are female, 88.3% of Malay ethnicity, 54% have education up to secondary school, and 40% are living alone without spouses. The prevalence of depression among elderly was high 39.4%. The mean mental health literacy score was 105 (SD: 19.4). There is a significant association between the literacy score and depression. Conclusion: Overall, the prevalence of depression among elderly was high at 39.4% and significantly associated with literacy score. Those with severe depression have lower literacy score, and the respondents are majority from the lower socioeconomic group. Apart from healthcare equity and equality, the mental health literacy and awareness among the elderly need to be addressed.